Methodology and Results Analysis of Effect and Economic Evaluations Related to Pharmaceutical Care Practice in China: A Recent Review - Wei, Chunyan; Li, Ruofei; Wu, Zhiang; Xiao, Guirong; Hu, Ming (Indian Journal of Pharmaceutical Education and Research, 2024)
Background To evaluate the value of pharmaceutical care, and sort out the existing problems in the current researches. Materials and Methods We established the research strategy and searched seven databases. Two reviewers independently screened the studies, extracted data, conducted the statistical analysis and assessed the quality of full economic evaluations. The pharmaceutical care was divided into 9 types based on the relevant standards of Chinese Hospital Association. Results 332 studies were included. The methods were mainly cohort studies (n=187, 56.32%), and followed by randomized controlled trials (n=124, 37.35%). Only 23 studies were conducted as full economic evaluations. The Quality of Health Economic Studies score was 61.22±12.80. The most commonly used effect indicators included length of hospital stay (n=166, 50%), prescription rationality rate (n=166, 50%), incidence of adverse reactions (n=117, 35.24%) and course of medication (n=107, 32.23%). For economic indicators, the cost of medication (n=269, 81.02%) and hospitalization (n=113, 34.04%) were the most frequently used indicator. The research results showed that pharmaceutical care could improve the therapeutic effect. 91.45% and 81.42% of the studies revealed that pharmaceutical care could reduce the cost of medication and hospitalization. Conclusion Pharmaceutical care can improve the therapeutic effect and save the cost. However, the methodology of pharmaceutical care effect and economic evaluation needs to be further improved.
Keywords: Review; Pharmaceutical care; Effect; Economic evaluation; Methodology